Kirsten Kjær – skæv på alle fronter - Jørgensen, Ulla Angkjær (Kvinder, Køn & Forskning, 2006)
The article discusses the construction of the art canon from gender studies perspective. The point of departure is taken from the marginalised perspective of the Danish artist Kirsten Kjær. The author does not answer the question of whether or not Kirsten Kjær should be included in the canon, but examines the mechanisms of exclusion that has contributed to marginalisation of her work within the established canon. The paper’s hypothesis is that Kjær is queer in different respects: she is a female artist, she does not care about the art discouses of her time, and she presents an alternative image of the gender contract of her time.